Shakespeare: The Authorship Question, a Bayesian Approach [reprinted from 2008] - Sturrock, Peter (Journal of Scientific Exploration, 2017)
Bayesian probability theory can be helpful in organizing the multiple evaluations required in analyzing complex problems that involve the comparison of several hypotheses on the basis of several datasets. The problem of deciding the authorship of the Shakespeare literary material falls under this heading. We here discuss just one aspect of this major problem: whether or not the available evidence indicates that “William Shakspere,” of Stratford-upon-Avon, was a writer. We consider 24 known writers who lived in England at the same time as Shakspere. For each of these writers, and for Shakspere, we follow Price in considering whether or not there exists evidence in each of 10 categories relevant to the literary profession. We find that there is evidence conforming to at least 3 categories for each comparison author, but none for Shakspere. We evaluate the probability, based on this information, that Shakspere was a writer similar to the 24 comparison writers. According to this analysis of Price’s data, we find that there is only one chance in 100,000 that Shakspere was a writer. These considerations support the heretical view that Shakspere was not the author of the Shakespeare material. Keywords: Shakespeare—statistics—probability